Incorporating endorectal MR elastography into multi‐parametric MRI for prostate cancer imaging: Initial feasibility in volunteers. Issue 5 (13th February 2013) - Arani, Arvin; Da Rosa, Michael; Ramsay, Elizabeth; Plewes, Don B.; Haider, Masoom A.; Chopra, Rajiv
Abstract : Purpose: To investigate the tolerability and technical feasibility of performing endorectal MR elastography (eMRE) in human volunteers within the representative age group commonly affected by prostate cancer. Materials and Methods: Endorectal MRE was conducted on seven volunteers in a 1.5 Tesla (T) MR imager using a rigid endorectal coil. Another five volunteers were imaged on a 3T MR imager using an inflatable balloon type endorectal coil. Tolerability was accessed for vibration amplitudes of ±1–50 μm and for frequencies of 100–300 Hz. Results: All 12 volunteers tolerated the displacements necessary to successfully perform eMRE. Shear waves with frequencies up to 300 Hz could propagate across the entire prostate using both coil designs. Conclusion: The results of this study motivate further investigation of eMRE in prostate cancer patients to help determine if there is an added value of integrating eMRE into existing multi‐parametric prostate MRI exams. J. Magn. Reson. Imaging 2013;38:1251–1260. © 2013 Wiley Periodicals, Inc.